2012
DOI: 10.1007/s11743-012-1373-9
|View full text |Cite
|
Sign up to set email alerts
|

Application of Green Commercial Surfactant in Preparing Purely Acrylic Latex via Semi‐continuous Seeded Emulsion Polymerization

Abstract: Nonylphenol ethoxylates (NPEOs) are widely used as surfactants for emulsion polymerization and for post adding stabilization for latex applications in formulations with high filler content. However, NPEOs are bioaccumulative and persistent in the environment while nonylphenol, the breakdown product of NPEs, is an endrocrine disruptor. Therefore, it has been recommended to ban technical processes using NPEOs as surfactants. The acrylic polymer latex was prepared via semi-continuous seeded emulsion polymerizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The structure of the resultant acrylic polymer latex was confirmed with Fourier transform infrared spectroscopy spectrum. Differential scanning calorimetry confirmed that the resultant latex was a kind of random copolymer and the consistency among the chain segment was fairly good [16].…”
Section: Acrylic Polymer Latex Emulsified With Apgmentioning
confidence: 83%
“…The structure of the resultant acrylic polymer latex was confirmed with Fourier transform infrared spectroscopy spectrum. Differential scanning calorimetry confirmed that the resultant latex was a kind of random copolymer and the consistency among the chain segment was fairly good [16].…”
Section: Acrylic Polymer Latex Emulsified With Apgmentioning
confidence: 83%
“…Furthermore, SDBS and NPEOs remained in the environment. 10,11 Thus, there is a demand for biodegradable surfactants in the production of polymer latexes from a social and environmental viewpoint. 10,11 Disodium laureth sulfosuccinate (AEMES) anionic surfactant has good biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Thus, there is a demand for biodegradable surfactants in the production of polymer latexes from a social and environmental viewpoint. 10,11 Disodium laureth sulfosuccinate (AEMES) anionic surfactant has good biocompatibility. Beta-cyclodextrin (b-CD) has been widely used in the emulsion polymerization due to its non-toxicity, biodegradation, sustainability, and good emulsification effect.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, environmental friendly alcohol ethoxylates(AEO-9), sulfosuccinic acid alkyl polyoxyethylene monoester disodium salt (A-102) and sorbitan monooleate (Span 80) instead of traditional APEO were chosen as surfactants in polymerization. Our research group also prepared polymer latexes emulsified with DSB and alkyl polyglycosides [5,6]. However, the above studies are focused on the replacement of NPEOs.…”
Section: Introductionmentioning
confidence: 99%